Survivin overexpression via adeno‐associated virus vector Rh10 ameliorates ischemic damage after middle cerebral artery occlusion in rats. (10th October 2018) - Sehara, Yoshihide; Inaba, Toshiki; Urabe, Takao; Kurosaki, Fumio; Urabe, Masashi; Kaneko, Naoki; Shimazaki, Kuniko; Kawai, Kensuke; Mizukami, Hiroaki
Abstract: Survivin, a member of the inhibitors of apoptosis protein gene family, inhibits the activity of caspase, leading to a halt of the apoptotic process. Our study focused on the neuroprotective effect of survivin after transient middle cerebral artery occlusion (MCAO) with intraparenchymal administration of an adeno‐associated virus (AAV) vector. His‐tagged survivin was cloned and packaged into the AAV‐rh10 vector. Four‐week‐old Sprague–Dawley rats were injected with 4 × 10 9 vg of AAV‐GFP or AAV‐His‐survivin into the right striatum and were treated 3 weeks later with transient MCAO for 90 min. Twenty‐four hours after MCAO, functional and histological analyses of the rats were performed. The result showed that rats that had been treated with AAV‐green fluorescent protein (GFP) and those that had been treated with AAV‐His‐survivin did not show a significant difference in neurological scores 24 hr after MCAO, however, infarction volume was significantly reduced in the AAV‐His‐survivin group compared to that in the AAV‐GFP group. Although the neutrophil marker myeloperoxidase did not show a significant difference in the ischemic boundary zone, cells positive for active caspase‐3 and terminal deoxynucleotidyl transferase‐mediated deoxyuridine triphosphate nick end labeling were significantly decreased in the AAV‐His‐survivin group. In conclusion, survivin overexpression in the ischemic boundary zone induced by using an AAV vector has the potential for amelioration of ischemic damage via an antiapoptotic mechanism. Abstract : Rats were injected with 4×10 9 vg of adeno‐associated virus (AAV)‐green fluorescent protein (GFP) or AAV‐His‐survivin into the right striatum and were treated three weeks later with transient middle cerebral artery occlusion (MCAO) for 90 minutes. Twenty‐four hours after MCAO, functional analysis did not show significant difference. Histological analyses showed that AAV‐His‐survivin treatment significantly reduced the infarction volume and decreased apoptotic markers in the ischemic boundary zone, but not the neutrophil infiltration.